Promoting the Accountability of Secondary School Principals of Hormozgan Province: Analysis of Dimensions and Components with a Qualitative Approach - Ahmadi Tefakani, Soheila; Bagheri, Mehdi; Ghourchiyan, Nadergholi; Sabahizadeh, Mahmoud (Iranian Journal of Educational Sociology, 2022)
Purpose: The efficiency of various organizations, especially educational organizations, depends to a large extent on the accountability of their principals. Therefore, the aim of the present research was to analyze the dimensions and components of promoting the accountability of secondary school principals.Methodology: This was an applied qualitative study. The study population included academic experts in educational management and educational sciences of Hormozgan province in 2020-2021. According to the principle of theoretical saturation, the sample size was estimated to be 10 individuals who were selected by purposive sampling method. The data collection instrument included a semi-structured interview. The validity of the above instrument was confirmed by the triangulation method and its reliability was calculated 0.85 using intercoder agreement coefficient. Finally, data analysis was carried out by open, axial and selective coding method in MAXQDA ver. 2018.Findings: The results of the present research showed that promoting the accountability of secondary school principals consisted of 32 indices, 9 components and 3 dimensions as follows: social accountability with two components of commitment to others and justification of an action to others, organizational accountability with four components of monitoring mechanisms, reporting, downward accountability and internal accountability, and functional accountability with three components of individual accountability, transparency and participation. Finally, the model of promoting the accountability of secondary school principals was drawn.Conclusion: According to the results of the current research, in order to promote the accountability of secondary school principals, it is necessary to promote social, organizational, and functional accountability dimension and their indices and components.